Approaching Consumer Culture Global Flows and Local Contexts (International Series on Consumer Science,, 2018)
This fascinating collection analyzes the impact of Western consumer culture on local cultures and consumption in Southeast Europe and East Asia. Cultural, historical, economic and sociopolitical contexts are examined regarding buying behaviors, usage and customization practices and consumer activism, specifically in Bulgaria, Serbia, and Romania as cultures continue to evolve in the post-socialist era, and in China and Japan as a continuation of movements toward modernity and progress. Surprising and thought-provoking contrasts stand out as consumers balance the global with the local in terms of clothing, technology, luxury items, and food. All chapters feature a wealth of empirical and cross-cultural data, and the presentation is framed by Professor Mike Featherstone's theoretical essay on the origins of consumer culture and the consequences of two hundred years of increasing consumption for the human condition and the future of the planet. Included in the coverage: "You are a socialist child like me": Goods and Identity in Bulgaria Consumer Culture from Socialist Yugoslavia to Post-Socialist Serbia: Movements and Moments Preserves Exiting Socialism: Authenticity, Anti-Standardization, and Middle-Class Consumption in Post-Socialist Romania Modernization and the Department Store in Early 20th-Century Japan: Modern Girl and New Consumer Culture Lifestyles A Cultural Reading of Conspicuous Consumption in China Approaching Consumer Culture broadens the cultural anthropology literature and will be welcomed by Western and Eastern scholars and researchers alike. Its depth and accessibility make it useful to university courses in cultural anthropology, cultural studies, and sociology.